Performance analysis and optimization for coverage classes updating mechanism of narrow-band internet of things - Xin JIAN; Yuqin LIU; Yixiao WEI; Jian SONG; Fang WANG; Shu FU; Xiaoheng TAN (Tongxin xuebao)
A Markov chain model with coverage classes as state variables was established to describe the dynamics of the coverage classes updating mechanism of narrow-band internet of things (NB-IoT).An optimization model to minimize average probability of access failure as well as average power consumption was formulated,with which the effects of preamble repetition number,system load and global maximum transmission number on the optimal configuration of maximum transmission number of each coverage class was analyzed.Numerical analysis results show that the maximum transmission number of normal coverage and extended coverage have a great influence on the system performance and their value ranges should be set within[1,5]and[1,7]respectively.However,the maximum transmission number of extreme coverage has little influence on the system performance,its value could be any one in[1,10]but the recommended value is 1.In addition,the average power consumption of the model that introduced coverage classes’ rollback mechanism is about 95% lower than the model proposed by 3GPP.